Unraveling the self: How postmodern philosophy reshaped the narrative of personal identity - Diana MIHEȘ (Studia Universitatis Babeș-Bolyai. Philosophia)
This paper examines the philosophies of Jacques Derrida, Michel Foucault, Gilles Deleuze, and Judith Butler, focusing on their insights into identity and individualism. While self-help literature often advocates fixed identities, this study argues for an alternative: existence as constant transformation, challenging stagnation in personal growth. Using a materialist lens, it explores identity through interactions of internal and external experiences with power dynamics. Postmodernists collectively highlight the self’s fluidity and its perpetual evolution. The goal is to assess their influence on understanding the self and explore implications for future narratives on identity.